Tuning Magnetic Property and Autophagic Response for Self‐Assembled Ni–Co Alloy Nanocrystals. (25th June 2013) - Dong, Liang; Liu, Yun; Lu, Yang; Zhang, Li; Man, Na; Cao, Liang; Ma, Kai; An, Duo; Lin, Jun; Xu, Yun‐Jun; Xu, Wei‐Ping; Wu, Wen‐Bin; et al.
Abstract Induction of autophagy is a common response of cells upon exposure to nanomaterials and represents both a safety concern and an application niche for engineered nanomaterials. Herein, it is reported that the magnetic property and the autophagy‐inducing activity for Ni–Co alloy nanocrystal (NC) assemblies can be differentially "tuned" through altering the material composition. A series of Ni–Co alloy NC assemblies, composed of nanoparticles (NPs) with a size of about 30 nm, can be quickly synthesized under microwave irradiation in aqueous solution. A controllable self‐assembling effect is observed due to the strong magnetic moment of NPs and external magnetic field. Interestingly, the saturation magnetization (Ms) shows a 'roller coaster' effect with varying component molar ratio, while the autophagy‐inducing activity and toxicity of these alloy NCs presents an elevated tendency with the increase of nickel component. The autophagic response partly contributes to the observed cellular toxicity of the NC assemblies, as inhibition of autophagy partially but significantly reduces toxicity. Therefore, through tuning the composition of the alloy, optimal Ni–Co NCs satisfying the needs of different applications such as diagnostic imaging (maximum magnetization and low autophagic response) or magnetically‐directed cancer cell killing (maximum autophagic response and sufficient magnetization) may be designed and developed.